ESTABLISHING A POSITIVE LEARNING ENVIRONMENT FOR ESL STUDENTS - Turdiyeva Rushona Yusup qizi; Norsoatova Mohinur Ziyadulla qizi (Лучшие интеллектуальные исследования, 2023)
This paper aims to examine the impact of the learning environment on ESL( English as a second language) students’ language acquisition. It is important to outline the role of the language atmosphere in the ESL classroom that should contribute to the development of students’ language skills. The authors suggest that if ESL teachers know how to create an appropriate and stimulating learning environment, the learning and teaching process will be more effective and productive. Thus, it should enhance and influence students’ attention, motivation, and academic achievements of ESL students.